Types and Institutional Design Principles of Collaborative Governance in a Strong-Government Society: The Case Study of Desertification Control in Northern China. Issue 4 (2nd October 2017) - Yang, Lihua
ABSTRACT: Although various actors participate in modern environmental and social governance, the types and mechanisms of the participation and collaboration of these actors have received little scholarly attention, especially in a society influenced by strict government policies. Based on a case study of 12 field sites and a systematic review of an additional 16 sites reported in the literature on desertification control in northern China, this study identified four types of collaboration and determined Type I (Strong Government with Strong Nongovernmental Participants) to be the best for desertification control performance, Type IV (Weak Government with Weak Nongovernmental Participants) to be the worst, and Type II (Strong Government with Weak Nongovernmental Participants) and Type III (Weak Government with Strong Nongovernmental Participants) to be tied for second place. This study also proposed eight principles for effective collaboration that addressed (1) the effective participation of multiple actors with enough support resources; (2) open and democratic forums for multiple-actor collaboration; (3) targeted, organized, systematic, and persistent collaborative activities; (4) effective mechanisms for discussion, communication, and shared learning; (5) effective trust-building mechanisms; (6) effective mechanisms of realization and increase of potential gains and fair distribution of benefits; (7) effective conflict resolution mechanisms; and (8) experiment-extension governance methods.